Efficient Micropropagation and Genetic Fidelity Assessment of In vitro Raised Dragon Fruit (Hylocereus spp.) using ISSR Markers (Plant Tissue Culture and Biotechnology, 2026)
An efficient in vitro regeneration protocol was developed for two dragon fruit species (Hylocereus polyrhizus and Hylocereus undatus) widely cultivated in Bangladesh. The highest percentage (100%) of explants responded to shoot induction and maximum number of multiple shoots (12.4 ± 1.14 and 14.2 ± 1.14) and highest length of shoots (6.70 ± 1.50 and 5.70 ± 1.50 cm) were obtained in MS + 2.0 mg/l BAP + 0.5 mg/l NAA. The in vitro regenerated and proliferated shoots were transferred to ½ strength of MS with 0.8 mg/l NAA where 100% shoots were produced roots. The maximum number (7.5 ± 0.12 and 8.8 ± 0.4) and highest length (7.4 ± 0.3 and 5.8 ± 0.2 cm) of roots were found in this medium. After transplantation to soil the survival rate of in vitro regenerated plantlets was 100%. No ISSR polymorphism in the micropropagated plants was detected, while 3 Inter Simple Sequence Repeat (ISSR) markers were used in order to look for any somaclonal variation among in vitro-derived plants, demonstrating the high level of genetic fidelity in the plantlets produced by the regeneration technique reported in this work.Plant Tissue Cult. & Biotech. 36(1): 37-47, 2026 (June)